(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
The Musi River is the largest and longest river in South Sumatra. The development of population activities in the Musi River Basin can affect river water quality and can cause pollution. The high level of industrial activity and households along the Musi River causes a decrease in environmental quality in the Musi River Basin. The declining quality of aquatic environment can be seen from the presence of phytoplankton. Based on this, further research is needed to determine the extent of pollution in the Musi River Basin. The purpose of this study is to assess saprobitas along the Musi River Basin based on SI (Saprobic Index) value and knowing the level of water pollution using saprobitas water assessment. This study uses plankton as a bioindicator of aquatic organic pollution. This study uses an exploratory design with survey methods, and the determination of sampling stations by purposive sampling method. The results showed abundance of phytoplankton in the waters of the Musi River in the range of 123 to 2581 cells.liter-1 or an average of 1397 cells.liter-1. The Saprobic index in the waters of the Musi River ranges from 0.631 to 1, classified in the phases of the microbial, namely β-Mesosaprobic, so that the waters of the Musi River are classified as mild.